MANAJEMEN SUMBER BELAJAR DALAM KONTEKS PENDIDIKAN MODERN - nabila sidqi alya; Athifah Lutfia; Sulkifli (As-Sulthan Journal of Education, 2025)
This article discusses the concept, characteristics, benefits, and digital transformation of learning resources in the modern education context. It highlights how educators can optimize diverse learning resources to improve the quality of education. The study uses a literature review method and concludes that effective learning resources should be relevant, accessible, interactive, flexible, and continuously updated.